Investigation of plasma-slag processes in special and ladle electrometallurgy of steel - Zhdanovsky, A.A.; Shapovalov, V.A.; Melnik, G.A.; Zhirov, D.M.; Prikhodko, M.S.; Odintsova, L.G. (Современная электрометаллургия, 2008)
Theoretical analysis made it possible to consider advantages of the progressive technology of steelmaking and determine specificity of main processes of the plasma-slag metallurgy, calculate partial pressure of the components and composition of the vapor-gaseous phase above slag of the fluorite--lime and lime--alumina--silicate systems. Experimental investigations allowed specifying some peculiarities of pyrometallurgical reactions in the gas (plasma)--slag--metal system in melting of ball bearing and stainless steels, low carbon iron, high carbon ferrochromium, and alloying of iron by chromium in case of application of the plasma-arc models as heat sources. Теоретический анализ дал возможность рассмотреть достоинства прогрессивной технологии сталеплавильного производства, определить специфику основных процессов плазменно-шлаковой металлургии, рассчитать парциальное давление компонентов и состав парогазовой фазы над шлаками флюорито-известковой и известково-глиноземно-силикатной систем. Экспериментальные исследования позволили уточнить некоторые особенности пирометаллургических реакций в системе газ (плазма)-шлак-металл при выплавке шарикоподшипниковой и нержавеющих сталей, низкоуглеродистого железа, высокоуглеродистого феррохрома и легирования железа хромом при использовании в качестве источника теплоты плазменно-дуговых моделей.